Measure and Evaluation of Financial Openness in China - Dou, Xiangsheng (International Journal of Economics and Financial Issues, 2016)
The key to China's economic openness is financial opening. Therefore, the correct measurement of China's financial openness is important for reform and opening up and the formulation and implementation of associated policies in China. This paper develops the indexes of financial openness to measure and evaluate financial opening level in China with the data from 2007 to 2013. The research results indicate that China's financial openness has reached a certain level at the current stage. Especially, a few of financial sectors have reached a relatively high openness level. On the whole, financial openness in China is in the middle level compared with the rest of the BRIC countries. However, China's financial openness is relatively low compared with the developed countries such as the Europe and the United States, showing that the degree of financial openness in China has yet to be further improved and enhanced. Keywords: financial openness, measure indexes, financial market openness, capital and financial account openness, financial service trade openness JEL Classifications: F33, G28